Olecranon fractures: applied anatomy, clinical assessment and evidence-based management. (2nd February 2022) - Karthikappallil, Dileep; Cash, Thomas; Fischer, Jochen; Waseem, Mohammad
Abstract : Olecranon fractures are common injuries, making up 10% of all fractures of the upper limb. They usually result from a fall from standing height in older people, or from a direct blow in young people. The olecranon's superficial location, with poor soft tissue and muscle protection, make it liable to fracture following direct impact. Factors such as the degree of initial force and the quality of the patient's bone result in a range of injury patterns, from simple undisplaced fractures to complex open fracture dislocations. In the context of high energy trauma, the patient should first be assessed for life-threatening injuries. A thorough history and clinical examination including neurovascular assessment should then be completed. Antero-posterior and lateral X-rays are sufficient to confirm the diagnosis. Initial management includes immobilisation in an above elbow backslab, a sling and analgesia. Owing to the pull of the triceps muscle which attaches to the tip of the olecranon, fracture displacement is common and surgical intervention is often required, usually with good outcomes. Surgical techniques include tension band wiring, open reduction internal fixation with a pre-contoured locking plate and tension band suture fixation. Undisplaced fractures or displaced fractures in older patients can be managed conservatively with an above elbow cast for 4 weeks. This article covers applied anatomy, initial presentation, clinical assessment and evidence-based management.